Developing authentic assessment instruments for music ensemble learning - Sundari, Regina; Ardipal (Universitas Jambi, Indonesia, 2025)
The aims of this research were (1) to explain the steps or process of developing authentic assessment instruments that are relevant for use in music ensemble learning, (2) to reveal the validity and reliability of authentic assessment instrument models, (3) to evaluate the practicality of authentic assessment instrument models, and (4) to explain the effectiveness of authentic assessment instrument models in music ensemble learning. The method used was the R&D model with the ADDIE approach: analysis, design, development, implementation, and evaluation. Data were collected through observation, questionnaires, and tests. Data analysis was carried out using qualitative and quantitative approaches. Data processing was carried out using SPSS version 22. The research results showed that previously, teachers used conventional models. The validity test for authentic assessment instruments in music ensemble learning scored 89.3, the practicality test scored 87.4, and the effectiveness test scored 89.4. It indicates that the authentic assessment instrument model is suitable for use.